CD73 facilitates invadopodia formation and boosts malignancy of head and neck squamous cell carcinoma via the MAPK signaling pathway. Issue 8 (16th June 2022) - Xue, Feifei; Wang, Tianxiao; Shi, Hao; Feng, Hongjie; Feng, Guanying; Wang, Ruixia; Yao, Yao; Yuan, Hua
Abstract: Elevated adenosine generated by CD73 (ecto‐5′‐nucleotidase; NT5E) could boost immunosuppressive responses and promote immune evasion in the tumor microenvironment. However, despite the immune response, CD73 could also promote tumor progression in a variety of cancers, and the nonimmunologic role and corresponding molecular mechanism of CD73 involved in head and neck squamous cell carcinoma (HNSCC) progression are not well characterized. Here, we demonstrated that CD73/NT5E is overexpressed in HNSCC tissues and predicts poor prognosis. Suppression of CD73 inhibited the proliferation, migration, and invasion of HNSCC cell lines (CAL27 and HN4) in vitro and in vivo. Gene set variation analysis (GSVA) and gene set enrichment analysis (GSEA) predicted that CD73 may be involved in invadopodia formation and MAPK signaling activation. As expected, knockdown of CD73 inhibited the MAPK signaling pathway, and the suppressive effect of CD73 knockdown on proliferation, migration, invasion, and invadopodia formation was reversed by a MAPK signaling activator. Our results suggest that CD73 could promote the proliferation, migration, invasion, and invadopodia formation of HNSCC via the MAPK signaling pathway and provide new mechanistic insights into the nonimmunological role of CD73 in HNSCC. Abstract : Despite immunomodulating role, corresponding molecular mechanism of CD73 involved in HNSCC progression are not well characterized. In this work, We found that CD73 was up‐regulated in HNSCC tissues and could serve as independent prognostic factor. Based on the result of GSEA and GSVA, we found that CD73 take part in the invadopodia formation of HNSCC and activation of MAPK signaling pathway may account for the tumor promoting role of CD73.